The Future of Collaboration: What Interprofessional Training Includes AI and Why It Matters for Digital Health - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The rapid and pervasive integration of Artificial Intelligence AI is fundamentally reshaping professional landscapes, with its impact being particularly tran...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care